Endoscopic management of polyposis syndromes: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - van Leerdam, Monique E.; Roos, Victorine H.; van Hooft, Jeanin E.; Dekker, Evelien; Jover, Rodrigo; Kaminski, Michal F.; Latchford, Andrew; Neumann, Helmut; Pellisé, Maria; Saurin, Jean-Christophe; Tanis, Pieter J.; Wagner, Anja; Balaguer, Francesc; Ricciardiello, Luigi (Endoscopy, 2019)
ESGE recommends that individuals with hereditary gastrointestinal polyposis syndromes should be surveilled in dedicated units that provide monitoring of compliance and endoscopic performance measures. Strong recommendation, moderate quality of evidence, level of agreement 90 %.ESGE recommends performing esophagogastroduodenoscopy, small-bowel examination, and/or colonoscopy earlier than the planned surveillance procedure if a patient is symptomatic. Strong recommendation, low quality of evidence, level of agreement 100 %.